O Instituto Cearense de Matemática (1954-1960): a origem do Instituto de Matemática da UFC - Barroso Junior, Eudes [UNESP] (2015)
This research has investigative and historiographical character and is meant to trace the origin of the Mathematical Institute of the Federal University of Ceará (IMUFC). The institute was created in 1960, based on the history of the Institute of Mathematics of Ceará (ICEM), founded in 1954, to which its existence is tied. Interviews and written statements of teachers involved in the creation of institutes and documentation of significant legal and institutional procedures that ensured the foundation and operation of both entities constitute the basis of this study. It was obtained an institutional graphic collection at the Federal University of Ceará. The results indicate that the performance of the Brazilian Mathematics Colloquium exerted influences in the historical process of consolidation of the ICEM. This consolidation made the ICEM update in mathematics the university professor in Ceará, which during the two years it worked as mandatory unit (1958-1959), until a definitive merger by UC, the UFC approved the order of their request for incorporation. Therefore, the IMUFC is originated from the ICEM. This fact is not very common in the history of the creation of mathematical institutes in federal Universities in Brazil, especially when attention is called to the fact that The ICEM was constituted as a civil non-profit society. Therefore, to detail the events concerning the creation of the institutes contributes to the knowledge of the history of institutions in Brazil